Development Diagnostik Of Three Tier Multiple Choice Diagnostic Test Instrument To Assess Learners' Ability On Static Electricity Material - Astuti, Rika; Kadri, Muhammad (Universitas Negeri Medan, 2024)
This study aims to determine the feasibility and ability of learners to the instruments developed. This research was conducted at SMA Negeri 6 Pematangsiantarcarriedin the odd semester of the 2023/2024 academic year. The type of research used is R & D (Reaserch and Development) using 3D models. The study was conducted on students who have studied static electricity materials. The samples used in this study were 36 students from Class XII-IPA 3 taken byrandom sampling. Data collection techniques in this study is by way of interviews, tests, and provide a response questionnaire. Data analysis was performed using the person correlation equation with diagnostic tests. The results of this study is a test instrument to measure the ability of students in SMA Negeri 6 Pematangsiantar on static electricity as many as 20 items of diagnostic questionsthree tier multiple choice. The item is already valid measured by the estimated product moment, has a high level of reliability with a value of 0.712, the difficulty level of the item is good. The results of the analysis of the problem items and the analysis of the ability of students showed that the test instruments used are effective in measuring the ability of students in SMA Negeri 6 Pematangsiantar on static electricity.